Influence of Demographic Disparities on Seat Belt Compliance in an Urban Area (Washington, DC). Issue 1 (January 2023) - Arhin, Stephen A.; Manandhar, Babin; Anderson, Melissa
This study evaluated the potential influence of demographic factors on seat belt compliance rates in an urban area. Washington D.C., which is the capital of the United States, is an urban area with mixed and diverse population. The city (and all states) conducts seat belt compliance surveys annually as a requirement of the National Highway Traffic Safety Administration (NHTSA). This article used compliance rates obtained from the field for 2014 through 2020 and matched those with demographic data for the same timeframe. The demographic data for the city was obtained from the United States Census Bureau. Demographic variables including race, educational and income levels for the eight wards in Washington D.C. we extracted for analysis. Overall, seat belt compliance usage in Washington ranged from 93% to 95.7% between 2014 and 2020. Approximately 42.3% of its population are Caucasian while 43.9% are African Americans with the remaining being Asian, Hispanics and other races. In addition, seat belt usage was reported by ward. Using single factor analysis of variance, it was determined that compliance rates in the wards were not statistically influenced by race, educational level, or income level at 5% level of significance. However, when comparing yearly seatbelt compliance from 2014 to 2020, the compliance rates of 2014 versus 2019, and 2014 versus 2020 were determined to be statistically different. Seat belt use should be encouraged for everyone in all jurisdictions. The analysis shows that, in this urban area, the three demographic variables do not have any influence on the compliance rates.